2021
DOI: 10.1038/s41598-020-79077-5
|View full text |Cite
|
Sign up to set email alerts
|

Fixational eye movements abnormalities and rate of visual acuity and stereoacuity improvement with part time patching

Abstract: Residual amblyopia is seen in 40% of amblyopic patients treated with part-time patching. Amblyopic patients with infantile onset strabismus or anisometropia can develop fusion maldevelopment nystagmus syndrome (FMNS). The purpose of this study was to understand the effects of presence of FMNS and clinical subtype of amblyopia on visual acuity and stereo-acuity improvement in children treated with part-time patching. Forty amblyopic children who had fixation eye movement recordings and at least 12 months of fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In the current series, a combined treatment of occlusion and active vision therapy has been shown to improve the visual function in both anisometropic and strabismic amblyopia, demonstrating that this approach may be a good and integral option to provide a visual rehabilitation in amblyopia. Although some studies have demonstrated the ability of patching of providing some improvements in stereopsis and contrast sensitivity [ 23 , 24 , 25 ], there are other options in terms of active visual training that have also been shown to provide an effective rehabilitation of the binocular function of amblyopia, including perceptual learning training, accommodative and binocular function stimulation [ 4 , 5 ]. However, this does not mean that this active vision therapy is a substitute for patching [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current series, a combined treatment of occlusion and active vision therapy has been shown to improve the visual function in both anisometropic and strabismic amblyopia, demonstrating that this approach may be a good and integral option to provide a visual rehabilitation in amblyopia. Although some studies have demonstrated the ability of patching of providing some improvements in stereopsis and contrast sensitivity [ 23 , 24 , 25 ], there are other options in terms of active visual training that have also been shown to provide an effective rehabilitation of the binocular function of amblyopia, including perceptual learning training, accommodative and binocular function stimulation [ 4 , 5 ]. However, this does not mean that this active vision therapy is a substitute for patching [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this, fixational eye movements abnormalities, i.e. fusion maldevelopment nystagmus syndrome (FMNS) and nystagmus without FMNS have also been found to prevent and limit stereopsis improvements, respectively 57 , with no difference in the stereoacuity gain among amblyopic etiologies. Taken together previous reports and the present data, future investigations may consider proper fixation stability as a clinical requirement for visual improvements.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, astigmatism of more than 1.5 diopters 49 , and type of amblyopia 51 , 52 have also been implicated. Interestingly, fixation instability, relatively neglected in standard eye examination, has been associated with longer patching treatment 56 58 , poor stereopsis improvement, or lack thereof 57 , 58 , and a higher risk of amblyopic relapse 57 . Despite recent results 37 , 59 , 60 , a systematic understanding of limiting factors, especially for dichoptic approaches, is still lacking and these limitations might influence treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…We found that mild to moderate amblyopic patients with nystagmus were more likely to have absent stereopsis compared to patients without nystagmus 34 . We have also previously reported that amblyopic patients with microstrabismus and nystagmus were more likely to have poor recovery of stereopsis and require longer duration of amblyopia treatment despite improvement in visual acuity with patching treatment 19 , 23 , 35 . Thus, in agreement with the previous studies from our lab, in the current study we found that patients with nystagmus were more likely to have poor stereopsis recovery after strabismus repair despite having mild to moderate amblyopia.…”
Section: Discussionmentioning
confidence: 66%
“…We separately analyzed subjects without nystagmus and subjects with nystagmus, with methods previously used in our publications 7 , 19 , 20 , 23 . Fixational saccades in patients without nystagmus were defined as saccades produced during attempted fixation and quick phases in patients with nystagmus were identified using the unsupervised clustering method.…”
Section: Methodsmentioning
confidence: 99%